Ancient masonry structures within an integrated approach: the reinforced corbelled flat roofs of Umm el-Jimal. (23rd July 2020) - Al Rabady, Rama
Abstract : The historical development of structural engineering design remains a subject separate from other themes in the historical precedents in construction and building materials. Scientists and scholars deal with the engineering performance of historical masonry structures through the traditional 'geometry'- Galileo's 'strength of materials' theoretical dichotomy. Such approaches emphasize the role of two main aspects in understanding the stability of masonry buildings: form of the structure (arcuated or non-arcuated) and the performance of its building materials in tension and/or in compression. Both theories are questioned because they were not able to comprehensively acknowledge the role of a third important factor- the constructional and reinforcement systems. The study revisits Galileo's 'simple beam' theory and exmines the effect of 'strength of material' in relation to the 'geometrical' and 'reinforcement' criteria. It uses the case of Umm el-Jimal in Jordan because the entire city is built using the sole building material: basalt stone. It explores the different applications of this material in generating reinforced flat structural design through employing diverse corbelling constructional techniques. The study recommends an integrative 'material-geometry-construction' approach for masonry structures to ensure a comprehensive understanding of its stability, equilibrium, and safety. It is an approach that could assist structural scholars in their attempts to take precedents as a means to advance contemporary theories in structural engineering.